Designing Blue Ocean Strategy at UD Rejeki - Hans Hermanto (Universitas Ciputra Surabaya, 2023)
The property industry is an industry that has intense competition. The competition creates an oversupplied condition where there are more goods offered when compared to market demand. This condition causes market players in the property industry to tend to conduct price wars. This competition is also felt by UD Rejeki as one of the players in the property industry. In order to avoid this fierce competition, companies must present innovations. This research uses Blue Ocean Strategy as a tool to design strategies so that UD Rejeki can avoid market saturation and price wars, and become a sustainable company. The design of Blue Ocean Strategy in this study is designed through the Strategy Canvas, Value Innovation, and Four Action Frameworks. This research method uses interviews from various sources that have been selected using purposive sampling method. Interviews were conducted in a semi-structured manner and documentation was conducted using transcripts, photos, and voice recordings. Data validity and reliability were tested using source triangulation.